Can athletes benefit from difficulty? A systematic review of growth following adversity in competitive sport - Howells, K.; Sarkar, M.; Fletcher, D. (Progress in brain research, 234, 2017)
Research points to the notion that athletes have the potential to benefit from difficulty. This phenomenon—otherwise known as growth following adversity—has attracted increasing attention from sport psychology scholars. In this paper, we systematically review and synthesize the findings of studies in this area to better understand: (a) how growth has been conceptualized in competitive sport, (b) the theory underpinning the study of growth in sport performers, (c) the nature of research conducted in this area, and (d) the adversity- and growth-related experiences of competitive athletes. Following the application of inclusion criteria and methodological quality assessment, 17 studies were deemed suitable for inclusion in the systematic review. The findings of these studies are reviewed and synthesized in relation to study characteristics (viz. growth terminology, theoretical underpinning, study design, participant details, and data analysis), quality appraisal, adversity-related experiences (viz. negative events and experiences, and response to negative events and experiences), and growth-related experiences (viz. mechanisms of growth and indicators of growth). To facilitate understanding of growth following adversity in competitive sport, we address the definitions and theories that have informed the body of research, discuss the associated findings related to the adversity- and growth-related experiences of competitive athletes, and outline avenues for future research. It is hoped that this review and synthesis will facilitate understanding and inform practice in this area.